6-Aryl- and 6-heteroarylpurines via cyclotrimerization - Turek, Pavel; Hocek, Michal; Kotora, Martin (Nucleic acids symposium series (2004), 2008)
Transition metal complex catalysed cocyclotrimerization of 6-alkynylpurines 1 with various diynes 2 and 6-(diynyl)purines 4 with nitriles 5 enabled to synthesize series of substituted 6-arylpurines 3 and 6-heteroarylpurines 6 in good yields. The obtained 6-aryl- and 6-heteroarylpurines were tested for cytostatic activity.
Keywords: kobalt; Cell Line; nádorové buněčné linie; Mice; Cell Line, Tumor; Cobalt; Diynes; Cytostatic Agents; cytostatické látky; diyny; zvířata; Humans; Purines; puriny; myši; buněčné linie; nitrily; lidé; Nitriles; Animals